Momentum-resolved spin-conserving two-triplon bound state and continuum in a cuprate ladder - Tseng, Yi; Paris, Eugenio; Schmidt, Kai Phillip; Zhang, Wenliang; Asmara, Teguh Citra; Bag, Rabindranath; Strocov, Vladimir N.; Singh, Surjeet; Schlappa, Justine; Rønnow, Henrik M.; Schmitt, Thorsten (Communications Physics, 2023)
Studying multi-particle elementary excitations has provided unique access to understand collective many-body phenomena in correlated electronic materials, paving the way towards constructing microscopic models. In this work, we perform O K-edge resonant inelastic X-ray scattering (RIXS) on the quasi-one-dimensional cuprate Sr 14Cu 24O 41 with weakly-doped spin ladders. The RIXS signal is dominated by a dispersing sharp mode 270 meV on top of a damped incoherent component 400-500 meV. Comparing with model calculations using the perturbative continuous unitary transformations method, the two components resemble the spin-conserving ΔS = 0 two-triplon bound state and continuum excitations in the spin ladders. Such multi-spin response with long-lived ΔS = 0 excitons is central to several exotic magnetic properties featuring Majorana fermions, yet remains unexplored given the generally weak cross-section with other experimental techniques. By investigating a simple spin-ladder model system, our study provides valuable insight into low-dimensional quantum magnetism.
CRIS-Team Scopus Importer:2023-06-30